Hubungan Aktivitas Fisik dengan Indeks Massa Tubuh dan Lingkar Pinggang pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung Angkatan 2019 - Faizal Riza Nugraha; Eva Rianti Indrasari; Uci Ary Lantika (UNISBA Press, 2023)
Abstract. Sedentary lifestyle is an important cause of excess body weight and has implications for body mass index and waist circumference which can lead to an increase in the incidence of non-communicable diseases. This study aims to determine the relationship between physical activity and body mass index and waist circumference. This study used a cross-sectional method, data were obtained from self administered questionnaire of the Global Physical Activity Questionnaire (GPAQ) and Google Form of anthropometric measurements in the form of body mass index and waist circumference From Bandung Islamic University Medical Faculty students population. Participants were obtained based on consecutive sampling method, and the data were processed using the Kolmogorov Smirnov test. Participants of the study was students from year 1 to year 3? Consist of 130 respondents. The results showed there was a significant relationship between physical activity and body mass index (p-value <0.05), and the relationship between physical activity and waist circumference (p-value <0.01). Physical activity can affect changes in body mass index and waist circumference so that an increase in physical activity makes it possible to prevent an increase in body mass index and waist circumference thereby reducing the risk factors for non-communicable diseases such as diabetes mellitus, stroke, chronic kidney disease and cardiovascular disease so that it is recommended for students to increase physical activity. Keywords: Physical Activity, Body Mass Index, Waist Circumference. Abstrak. Perilaku hidup sedentary merupakan penyebab penting terjadinya berat badan berlebih dan berimplikasi terhadap indeks massa tubuh dan lingkar pinggang yang dapat mengakibatkan peningkatan angka kejadian penyakit tidak menular. Penelitian ini bertujuan untuk mengetahui hubungan aktivitas fisik dengan indeks massa tubuh dan lingkar pinggang. Penelitian ini menggunakan metode cross sectional, data diperoleh dari pengisian Global Physical Activity Questionnaire (GPAQ) dan pengukuran antropometri berupa indeks massa tubuh dan lingkar pinggang pada populasi mahasiswa Fakultas Kedokteran Universitas Islam Bandung Angkatan 2019 yang diperoleh berdasarkan consecutive sampling, data diolah menggunakan uji Kolmogorov smirnov. Hasil penelitian menunjukan bahwa dari seluruh responden (130 orang) terdapat hubungan yang signifikan antara aktivitas fisik dengan indeks massa tubuh (p-value <0,05), dan hubungan aktivitas fisik dengan lingkar pinggang (p-value <0,01). Aktivitas fisik dapat mempengaruhi perubahan indeks massa tubuh dan lingkar pinggang sehingga peningkatan aktivitas fisik memungkinkan untuk mencegah peningkatan dari indeks massa tubuh dan lingkar pinggang sehingga menurunkan faktor risiko terjadinya penyakit tidak menular seperti diabetes militus, stroke, penyakit ginjal kronis, dan penyakit kadiovaskular sehingga disarankan mahasiswa untuk meningkatkan aktivitas fisik. Kata Kunci: Aktivitas Fisik, Indeks Massa Tubuh, Lingkar Pinggang.